SYNTHESIS OF STAUROLITE IN MELTING EXPERIMENTS OF A NATURAL METAPELITE: CONSEQUENCES FOR THE PHASE RELATIONS IN LOW-TEMPERATURE PELITIC MIGMATITES - Garcia-casco A.; Haissen F.; Castro A.; El-hmidi H.; Torres-roldan R.L.; Millan G. (My University, 2003)
We document experiments on a natural metapelite in the range 650–775°C, 6–14 kbar, 10 wt?% of added water, and 700–850°C, 4–10 kbar, no added water. Staurolite systematically formed in the fluid-present melting experiments above 675°C, but formed only sporadically in the fluid-absent melting experiments. The analysis of textures, phase assemblages, and variation of phase composition and Fe–Mg partitioning with P and T suggests that supersolidus staurolite formed at (near-) equilibrium during fluid-present melting reactions. The experimental results are used to work out the phase relations in the system K2O–Na2O–FeO–MgO–Al2O3–SiO2–H2O appropriate for initial melting of metapelites at the upper amphibolite facies. The P–T grid developed predicts the existence of a stable P–T field for supersolidus staurolite that should be encountered by aluminous Fe-rich metapelites during fluid-present melting at relatively low temperature and intermediate pressures (675–700°C, 6–10?kbar for XH2O = 1, in the KNFMASH system), but not during fluid-absent melting. The implications of these findings for the scarcity of staurolite in migmatites are discussed.
Keywords: metapelites; migmatites; partial melting; P-T grid; staurolite